The evolution of precision agriculture and food safety: a bibliometric study - Xu, Jiahui; Cui, Yuanpei; Zhang, Shuhan; Zhang, Meiping (Frontiers in Sustainable Food Systems, 2024)
Food safety issues pose a significant threat to humanity. Precision agriculture leverages advanced technologies for real-time monitoring and management, improving agricultural productivity and sustainability while safeguarding food security. Nonetheless, acquiring a thorough comprehension of this continually shifting panorama remains of vital significance. This study conducts a comprehensive bibliometric review of precision agriculture and food safety, utilizing quantitative methods to identify past, current, and future evolution. Publications emerged in 1994 and began to rise significantly since 2019. Citation analysis verified influencing works and journals, whereas co-authorship analysis identified how authors, institutions, and countries collaborate in this field. Co-citation analysis then classified past and current hotspots into four clusters: remote vegetation monitoring techniques, technological innovations and agricultural decision-making, precision agriculture and sustainable development, and deep learning in agriculture. After that, the co-occurrence of keywords revealed emerging trends, such as precision cultivation and yield prediction, smart agricultural technology and food management, precision information for climate change adaptation, and precision agriculture and food security. The results provide valuable insights for scholars, policymakers, researchers, practitioners, and industry stakeholders, guiding future research directions and helping to address challenges in agriculture and food safety.